2022
DOI: 10.3390/ani12223081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Feeding Regimes and Postmortem Aging on Meat Quality, Fatty Acid Composition, and Volatile Flavor of Longissimus Thoracis Muscle in Sunit Sheep

Abstract: The effects of different feeding regimes on antioxidant activity, meat quality, fatty acid composition, lipid oxidation, and volatile matter production in the longissimus thoracis (LT) of Sunit sheep at 0, 24, 48, 72, and 96 h postmortem were investigated. The results showed that the activity of antioxidant enzymes, tenderness, water retention, and percentage of unsaturated fatty acids were significantly higher in the pasture-fed sheep (PF) than in the concentrate-fed sheep (CF) (p < 0.05). During postmorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…An increase in fat can decrease collagen content, which was also observed in the present study [44] Although the study found no significant differences in the content of SFA, MUFA, PUFA fatty acid groups and in the content of the main isomer of C18:2 cis-9, trans-11 linoleic acid either between fresh and aging meat or between the muscles studied, it should be noted that meat after aging in both GM and LL muscles was characterized by an increase in SFA content and a decrease in MUFA and PUFA (Table 3). A similar variation in fatty acid content during aging was obtained by Yang et al [11] in a study of m.l.d. muscle in Sunit sheep subjected to different feeding regimes.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…An increase in fat can decrease collagen content, which was also observed in the present study [44] Although the study found no significant differences in the content of SFA, MUFA, PUFA fatty acid groups and in the content of the main isomer of C18:2 cis-9, trans-11 linoleic acid either between fresh and aging meat or between the muscles studied, it should be noted that meat after aging in both GM and LL muscles was characterized by an increase in SFA content and a decrease in MUFA and PUFA (Table 3). A similar variation in fatty acid content during aging was obtained by Yang et al [11] in a study of m.l.d. muscle in Sunit sheep subjected to different feeding regimes.…”
Section: Discussionsupporting
confidence: 85%
“…Decreasing pH values in lamb meat with aging up to 35 days were recorded by Gramatina et al [13] in a study comparing the quality of beef, lamb and pig meat. A significant reduction of this parameter, but during 0 and 24 hours after slaughter, was recorded by Yang et al [11] in LT muscle of Sunit sheep, which the authors explained by the accumulation of lactic acid during the process of anaerobic glycolysis. In this studies, there was no effect of muscle on the pH value either in fresh meat and after 7 and 14 days of aging.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The cooking loss rate of the longissimus thoracis muscle in the concentrate-fed was significantly higher than that in the pasture-fed. (Yang et al, 2022) Finishing pigs A 2 9 2 factorial arrangement with two levels of valine and two levels of isoleucine constituted four dietary treatments Drip loss and cooking loss increased at higher levels of valine in the feed, and high levels of isoleucine reduced meat drip loss (Xu et al, 2020) Crossbred pigs Addition of different types and levels of selenium to feed for feeding, respectively…”
Section: Yangzhou Geesementioning
confidence: 99%